Interaction of the Anticancer Drug Abiraterone with dsDNA - Pronina, V.V.; Agafonova, L.E.; Masamrekh, R.A.; Kuzikov, A.V.; Shumyantseva, V.V. (Biomedical Chemistry: Research and Methods, 2022)
The electroanalytical characteristics of double-stranded DNA (dsDNA) and the complex of dsDNA and the antitumor drug abiraterone acetate (AA) were studied by differential pulse voltammetry. The effect of abiraterone acetate on dsDNA was shown, which was registered by alteration the intensity of electrochemical oxidation of purine heterocyclic bases guanine and adenine using screen printed electrodes modified with functionalized carbon nanotubes. The binding constants (Kb) of the [dsDNA-AA] complex for guanine and adenine were 1.63×104 M-1 and 1.93×104 M-1, respectively. The electrochemical coefficients of the toxic effect were calculated as the ratio of the intensity of the electrochemical oxidation signals of guanine and adenine, in the presence of abiraterone acetate to the intensity of the electrooxidation signals of these nucleobases without drug (%). At concentrations of abiraterone acetate exceeding 60 μM, a decrease in the currents of electrochemical oxidation of guanine and adenine by 50% or more is recorded. Based on the analysis of electrochemical parameters and values ​​of binding constants, an assumption was made about the mechanism of interaction of abiraterone acetate with DNA, mainly due to the formation of hydrogen bonds with the minor groove. An electrochemical DNA biosensor was first used to study the mechanism of interaction of the anticancer drug abiraterone acetate with dsDNA.